ORGANIZATIONAL DESIGN EFFECTIVENESS OF WEST SERAM DISTRICT GOVERNMENT IN STRUCTURE REVIEW - Rugaya Alhamid (BADATI, 2021)
This study aims to analyze the effect of organizational structure on the organizational design of the West Seram Regency Government. This study was designed using a qualitative approach with a positivism paradigm, which is based on a deductive logic system (hypothetico-deductive method). The type of research is a case study. The results showed that the dimensions of complexity in the SKPD organizational structure look wide horizontally and vertically high so that it is more complex. Similarly, the dimension of formality, has not touched its substance because there is no standardization of work, regulations and standard work procedures for employees in carrying out their duties and responsibilities. Meanwhile, from the centralized dimension, the decision-making and supervision processes have been handed over to each SKPD, although in the end the highest decision rests with the Regent of West Seram Regency.